1989
DOI: 10.1016/0304-4017(89)90043-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficacy of ivermectin against Heligmosomoides polygyrus (Nematospiroides dubius) in mice

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk Veterinary Parasitology, 32 (1989) The efficacy of ivermectin against Heligmosomoides polygyrus was investigated in 5 mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
(38 reference statements)
2
14
1
Order By: Relevance
“…Another study showed that 2.9 µmoles/kg of ivermectin delivered on day 10 P.I. effected ∼70% reduction in H. bakeri worm burdens [30]. We could not find comparable studies with H. bakeri and benzimidazoles, although we did find that mebendazole delivered for 7 consecutive days, starting day 9 P.I.…”
Section: Resultscontrasting
confidence: 59%
“…Another study showed that 2.9 µmoles/kg of ivermectin delivered on day 10 P.I. effected ∼70% reduction in H. bakeri worm burdens [30]. We could not find comparable studies with H. bakeri and benzimidazoles, although we did find that mebendazole delivered for 7 consecutive days, starting day 9 P.I.…”
Section: Resultscontrasting
confidence: 59%
“…Group 3 animals, as the challenge control group, were also treated in case there was a residual effect against the subsequent infection, although none was expected given the 4-week interval to infection (Wahid et al, 1989). Initially three groups (2, 4 and 5) were infected orally with 50 infective larvae of A. ceylanicum on day 0.…”
Section: Experimental Designmentioning
confidence: 99%
“…The yellow‐necked mouse population was monitored every 2 weeks from February to March, and from the first week of April until the middle of September, we selectively treated adult and subadult individuals with the anthelmintic Ivermectin (Ivomec ® , Merial, Merck Sharp & Dohme, Harlem, Netherlands) by injecting a subcutaneous dose of 10 mg kg −1 (Wahid et al. 1989).…”
Section: Parasite Manipulationmentioning
confidence: 99%
“…In a second random group of three trapping grids we treated only males and the three remaining grids were used as controls where no individuals were treated. We assumed that the drug efficacy lasted 11–15 days (Wahid et al. 1989) and as the prepatency period of H. polygyrus from egg to egg was 13–15 days long (Keymer 1985), each individual was treated once a month.…”
Section: Parasite Manipulationmentioning
confidence: 99%